O dano endotelial, tubular e de glicocálice na lesão renal aguda da leptospirose - Braz, Marcelo Boecker Munoz (2014)
: Leptospirosis is a common disease in tropical countries, and the kidney is one of the main target organs. Membrane proteins of Leptospira are capable of causing endothelial damage in vitro, but there have been no studies in humans evaluating endothelial glycocalyx damage in humans and its correlation with acute kidney injury (AKI). Methods: We performed a cohort study in an outbreak of leptospirosis among military personnel. AKI was defined in accordance to KDIGO standard. Biomarkers for tubular injury (NGAL), glycocalyx injury (Syndecan-1) and endothelial injury (ICAM-1) were measured in plasma, as well as other biochemical parameters in all patients. Multivaried linear analisys was conducted in the correlation of the difference between maximal and minimum serum creatinine (ΔSCr) or NGAL with independent factors. Results: AKI was diagnosed in 14 of 46 (30.4%) patients and 13 presented its mildest form (KDIGO stage 1). Leptospirosis was associated with higher levels of intercellular adhesion molecule-1 (ICAM-1; 483.1 ± 31.7 versus 234.9 ± 24.4 mg/L, P < 0.001) and syndecan-1 (73.7 ± 15.9 versus 21.2 ± 7.9 ng/mL, P < 0.001) compared with exposed controls. Patients with leptospirosis associated AKI had increased level of syndecan-1 (112.1 ± 45.4 versus 41.5 ± 11.7 ng/mL, P = 0.021) and ICAM-1 (576.9 ± 70.4 versus 434.9 ± 35.3, P = 0.034) compared with leptospirosis patients with no AKI. Association was verified between syndecan-1 and ICAM-1 with serum creatinine elevation and neutrophil gelatinase associated lipocalin (NGAL) levels. This association remained even after multivariate analysis including other AKI associated characteristics. Conclusion: Endothelial injury biomarkers are associated with leptospirosis-associated renal damage.